PENGARUH LATIHAN DRILL GROUNDSTROKE DAN FIXED TARGET TERHADAP PENINGKATAN FOREHAND GROUNDSTROKE TENIS LAPANGAN PUTRA USIA 12-18 TAHUN DI CLUB GOMES KLATEN TAHUN 2021 - Afaida Ahmad Dahlan; Untung Nugroho; Satrio Sakti Rumpoko (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2022)
The purpose of this study was to determine the effect of groundstroke drills and fixed target on the forehand groundstroke ability of boys aged 12-18 years at club Gomes Klaten in 2021. to find out which exercises were better between groundstroke drills and fixed target on forehand groundstroke techniques aged 12-18 years. at club Gomes Klaten in 2021. The results of this study (1) there is a significant effect between groundstroke drill exercises and fixed target on the results of forehand groundstroke ability in athletes aged 12-18 years at the Gomes Club Klaten in 2021. From the calculations that have been carried out the groundstroke drill group obtained a t value of 3.142 and the fixed target exercise group obtained a t value of 2.625, it was greater than t_(table 5%) which was 2.131. (2) Groundstroke drill exercises have a better effect on the ability of fixed targets on forehand groundstrokes in athletes aged 12-18 years at the Gomes Club Klaten in 2021. The increase in group 1 forehand groundstroke abilities (the group that received groundstroke drill training treatment) was 14.5 % > group 2 (the group that received the fixed target training treatment) which was 9.5%.